Pertumbuhan dan Hasil Tanaman Kacang Tanah terhadap Pemberian Air Cucian Beras Coklat di Lahan Rawa Lebak - Ahmad Riyadi; Nurul Istiqomah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
Peanuts is one type of secondary crop which ranks third after corn and soybeans. Peanuts have long been used as food, while by-products can be used as animal feed. In connection with the problem of lack of fertility in lebak wetland soil, in order to produce high production with good quality, efforts need to be made to add nutrients. Rice washing water has a high carbohydrate content. Carbohydrates can be an intermediary for the formation of the hormones auxin and giberelin. Two types of ingredients that are widely used in artificial growth stimulants. This study aims (i) to determine the growth response and yield of peanut plants to the provision of brown rice washing water on lebak wetland, (ii) to find out the best time interval for brown rice washing water for plant growth and yield peanuts on lebak wetland. This research was conducted in Banyu Tajun Pangkalan Village, Sungai Pandan Sub-District, Hulu Sungai Utara Regency from April to June 2013, using randomized complete design (CRD) with single factor. The factors studied were the brown rice washing water interval. The results showed that the treatment did not affect the observation of plant height and number of branches, and had a very significant effect on the variables observed in the number of crop pods, wet weight of crop pods, and dry weight of plant pods. The results of this study indicate that the best treatment is at p5 (6 days).